2012
DOI: 10.1021/ol300761q
|View full text |Cite
|
Sign up to set email alerts
|

[2]Pseudorotaxanes from T-Shaped Benzimidazolium Axles and [24]Crown-8 Wheels

Abstract: A new templating motif for the formation of [2]pseudorotaxanes is described in which T-shaped axles with a benzimidazolium core and aromatic substituents at the 2-, 4-, and 7-positions interact with [24]crown-8 ether wheels ([24]crown-8, dibenzo[24]crown-8, and dinaphtho[24]crown-8). The T-shape greatly enhances the association between axle and wheel when compared to simple imidazolium or benzimidazolium cations. A series of interpenetrated molecules are characterized by (1)H NMR spectroscopy and single crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…[6] More recently, we have developed two new recognition motifs for 24-membered crown ether wheels based on compact, T-shaped 2,4,7-triphenylbenzimidazolium [7] and Y-shaped 2,4,5-triphenylimidazolium axles [8] and successfully combined these units to prepare rigid axles for [2]rotaxane molecular shuttles. [9] This allowed us to create MOF UWDM-4 (University of Windsor Dynamic Material) for which it was demonstrated that the large-amplitude translational motion of a molecular shuttle could occur inside the organized lattice of a crystalline material.…”
Section: Introductionmentioning
confidence: 99%
“…[6] More recently, we have developed two new recognition motifs for 24-membered crown ether wheels based on compact, T-shaped 2,4,7-triphenylbenzimidazolium [7] and Y-shaped 2,4,5-triphenylimidazolium axles [8] and successfully combined these units to prepare rigid axles for [2]rotaxane molecular shuttles. [9] This allowed us to create MOF UWDM-4 (University of Windsor Dynamic Material) for which it was demonstrated that the large-amplitude translational motion of a molecular shuttle could occur inside the organized lattice of a crystalline material.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Almost all [2]rotaxane molecular shuttles that have been characterized to date, have large and flexible structures and functione fficiently in solution. [5] This motif was used to prepare H-shaped,d egenerate [2]rotaxane molecular shuttles, which exhibiting spontaneous shuttlingb etween two equivalent recognition sites in solution;t he rate couldb ec ontrolled by either acid-basec hemistry or lithium-ion coordination. The first new MIM template identified for this purpose was that between T-shaped 2,4,7-triphenyl-substituted benzimidazolium axles and 24-membered crown ether wheels.…”
Section: Introductionmentioning
confidence: 99%
“…The target suit[1]ane 6a was prepared as outlined in Scheme 2. The T-shaped benzimidazolium axle [ 1 – H][BF 4 ] was readily prepared using a previously reported method 17 and the appended crown ethers 4 and 5 were constructed via multiple-step syntheses. The bis(hydroxymethyl) substituted crown ether 2 was prepared according to a literature method 20 and brominated to afford the bis(bromomethyl) crown ether 3 which was alkylated to afford macrocycles 4 and 5 in yields of 91% and 71%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…16 In this regard, we developed a T-shaped benzimidazolium cation [ 1 – H] + which can act as an axle for the formation of [2]pseudorotaxanes with a wide variety of crown ethers including DB24C8 and BMP26C8 . 17 In the X-ray structure of [2]pseudorotaxane [ 1 -H⊂ DB24C8 ] + , the crown ether was found to be clamped around the T-shaped axle using ion-dipole, hydrogen-bonding and π-stacking interactions; Scheme 1. This interpenetrated structure could then be trapped by stoppering the end of the axle to form a [2]rotaxane; Fig.…”
Section: Introductionmentioning
confidence: 99%